2020
DOI: 10.1177/2280800020940279
|View full text |Cite
|
Sign up to set email alerts
|

Development of a phase change microcapsule to reduce the setting temperature of PMMA bone cement

Abstract: The aim of the current study is to alleviate the adverse effect of the strongly exothermic polymerization of polymethyl methacrylate (PMMA) bone cement in clinical applications. In this study, paraffin/poly(methyl methacrylate–methylene bisacrylamide) (paraffin/P(MMA-MBA)) phase change microcapsules (MPn; n = 1, 2) were developed via the emulsion polymerization method. The reduction of the maximum temperature of polymerization (Tmax) and physicochemical properties were evaluated after doping commercial PMMA ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The characteristic peaks observed in PCM2's spectrum at 2922 cm −1 and 2855 cm −1 are associated with the stretching vibrations of the C-H groups in methylene. The peak at 1464 cm −1 corresponds to the bending of the C-H chain in the methyl/methylene groups [43]. Additionally, the peak observed at 721 cm −1 is associated with the oscillation of the methylene groups [44].…”
Section: Chemical Structurementioning
confidence: 98%
“…The characteristic peaks observed in PCM2's spectrum at 2922 cm −1 and 2855 cm −1 are associated with the stretching vibrations of the C-H groups in methylene. The peak at 1464 cm −1 corresponds to the bending of the C-H chain in the methyl/methylene groups [43]. Additionally, the peak observed at 721 cm −1 is associated with the oscillation of the methylene groups [44].…”
Section: Chemical Structurementioning
confidence: 98%
“…Long-term problems include tumor regrowth that may necessitate repeat surgery. To solve thermal damage to the spinal cord, Xia et al 36 developed Paraffin/P(MMA-MBA) PCM using the method of emulsion polymerization. They found that doping PMMA with microcapsules decreases its T max and thus avoids the adverse effects of strong exothermicity during the PMMA setting process.…”
Section: Bone Cementmentioning
confidence: 99%
“…Long‐term problems include tumor regrowth that may necessitate repeat surgery. To solve thermal damage to the spinal cord, Xia et al 36 . developed Paraffin/P(MMA‐MBA) PCM using the method of emulsion polymerization.…”
Section: Bone Cementmentioning
confidence: 99%